Robotics Club Students Create Interactive Model of Ilse Teske Sculpture Park - Sant'Ana, Vanessa Lopes; Bottamedi, Venicio; Maffezzolli, Graziela (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This article describes the creation of an interactive model of the Ilse Teske Sculpture Park by students from 6th to 9th grade at Professor Georgina de Carvalho Ramos da Luz Elementary School. The project was born from an activity developed by the Educational Robotics Club, which aimed to integrate technology and education. Using Arduino robotics kits, the students applied concepts of computational thinking, digital culture, and programming to build an interactive replica of the park. The project also sought to promote the cultural heritage of Brusque, Santa Catarina, encourage creativity and innovation among students, and foster educational tourism in the city. There were some challenges, but the students persisted and completed the model. They successfully presented it at the 1st Education, Technology, Innovation, and Science Exhibition, where they won second place in the Tinkercad and Arduino categories.